Análisis y evaluación financiera del diario la hora compañía limitada de la ciudad de Loja periodo 2009 – 2010. Propuesta de mejoramiento - Guamán Macas, Jorge Luis (2012)
The financial analysis allows the evaluation of the operative behavior of a company, to diagnose the current situation and to predict future events that it allows to detect those fallacies on time and to give them solution to be able to reach the proposed managerial objectives. The use of this tool helps to interpret the operative behavior of a company appropriately, he/she gives to know the short term liquidity, its capital structure and solvency, and the profitability obtained during a certain countable period. The development of the present denominated work "ANALYSIS AND FINANCIAL EVALUATION OF THE NEWSPAPER THE HOUR LIMITED COMPANY OF THE CITY DE LOJA PERIOD 2009-2010. PROPOSAL OF IMPROVEMENT", it is framed in the execution of three specific objectives: To make a diagnosis of the current situation of the Countable Department - Financial of the Newspaper The Hour Branch Loja; to apply vertical, horizontal analysis and financial indicators to the states financial periods 2009-2010, and to outline the respective proposals of improvement according to the results obtained in the investigation, to improve the financial situation of the Newspaper The Hour Branch Loja. The diagnosis of the current situation of the Countable Department - Financial he/she was carried out it considering the development of the human resources, materials and technological of the Newspaper The Hour Branch Loja detecting some fallacies like selection processes of personal inadequate, use of a program countable non chord to the requirements of the company, incorrect distribution of the plant. For the financial analysis vertical analysis the same one was applied that he/she gave to know the structure of the Asset, Passive, Patrimony Revenues and so much Expenses of the General Balance and State of Losses and Earnings, are so it was determined that of 100% of the Total of Active, to the average Asset it corresponds him 48,16% integrated by Box-banks with 4,39%; you Count and Documents to Charge Clients with 17,22%, Other Bills to Charge Officials AND Employees with 18,86% and I inventory with 4.14%, to the Asset Current conformed pro machinery, Not plants and team, considering the respective depreciations belongs him 51.48%, here they stand out the item of Machinery and Team of Calculation. The PASSIVE ones are of 61,94%, of those which the 41. 99 are passive currents and the Non currents are of 19.96%, this represents the obligations that he/she has the company to short and I release term. The PATRIMONY is of 38,06%, formed by social Capital, the Reservation of Capital and Utility, what indicates the proportion that of resources characteristic with those that it counts the company in study. The revenues correspond to $1, 403,002.99 of these 98.85% belongs to the average Revenues for sales of services for publicity in Loja, Zamora and I Remove and the newspaper sales, The total EXPENSES of $1,371,866.05 of where the average expenditures correspond him 91,78% whose bills substitutes are Goods and Services of Consumption basic Remunerations with the and Other Expenses of Personal, the difference of these two groups gives an utility of 2.22%. The horizontal analysis, was applied to the bills of more attention to present significant changes in the march of the business; among these we have to Other Bills to charge Officials and Employees with an increment represented in their relative variation by 36933,29%, you Count and Documents to charge to clients with a decrease whose relative variation is of -21,40%, these bills correspond to its work capital the same one that should be assisted on time. The National Suppliers belonging to the group of the Passive sample an increment of 895,50% indicating new obligations with third and the Patrimony with an increase of 10,72%, it points out a favorable situation for the organization. The average revenues present an increment of 68.16%, because the newspaper sale and sale of services; they went superior to that of the previous year; the expenses present a growth of 6.78%; for the increment of the basic remunerations and bank expenses; the utility with a relative variation of 2510.79%, indicates a positive increment since for the company it contributes to improve its institutional capital. In the average reason it is of $1.07 in the 2009 and with $0,91 in the 2010 what indicates that in the year 2010 the result is smaller at 1. The sour test is of 0,93cents in the 2009 and the 0,81 cents in the 2010, this sample the times that the average asset covers to the passive current whose results are smaller at 1. The Yield of the one GNAWS and ROA, shows the earnings obtained by each dollar invested as a consequence of its Patrimony and Active, (it GNAWS; 15,66% and of 369,18% and ROA 2,82% and 59,13%) and the level of indebtedness in what refers to Passive totals on active total was of 63,23% in the 2009 and 37,79% in the 2010 and the Total Leverage of 171.96% (2009) and of 162.77% (2010). These diagnoses allowed to outline solutions that contribute to improve working of the company, subsequently they think about the respective conclusions and recommendations that stand out the points but outstanding of the investigation.